Development of characteristic airway bifurcations in cystic fibrosis. Issue 10 (3rd October 2021) - Bass, Karl; Thomas, Morgan L.; Kemner-van de Corput, Mariette P. C.; Tiddens, Harm A. W. M.; Longest, P. Worth
Abstract: The objective of this study was to develop mathematically described characteristic tracheobronchial bifurcations that are representative of aerosol transport and deposition in the intermediate airways of children with cystic fibrosis (CF), where bronchiectasis is a major contributor to changes in lung anatomy. Realistic airway models in the region of bifurcations B4-B7 were extracted from CT scans of children that were scored as having either low (CT-Low) or moderate (CT-Mod) CF lung disease and served as a basis for comparison with characteristic models. Aerosol deposition characteristics in these CT-extracted models were compared with a previously developed baseline stochastic individual path model (Baseline SIP), based on mathematically defined physiologically realistic bifurcations (PRBs), and new characteristic PRB geometries with modifications made to account for the CF disease state. The Baseline SIP models provided a poor approximation of aerosol deposition in the scan-extracted geometries, as expected. In contrast, the new characteristic (modified) PRB geometries adequately captured deposition consistent with the scan-extracted geometries across the two disease states considered for multiple particle sizes and inhalation flow rates. This was surprising considering that the modified PRB geometries, which can be mathematically specified, only captured an expanded bifurcation region and extended carinal curvature, both representative of bronchiectasis, and neglected asymmetry, surface roughness and non-circular branch cross-sections. In conclusion, the new characteristic PRB geometries adequately captured the deposition characteristics of scan-extracted airway models and can be implemented to represent airway structures in the intermediate and likely deeper lung regions of children with CF for future complete-airway modeling studies. Copyright © 2021 American Association for Aerosol Research